Double Flip Technique for Graft Transfer in Autograft Pterygium Surgery - Emrah Öztürk; Abuzer Gündüz (Türk Oftalmoloji Dergisi, 2023)

(untitled)
A 50-year-old man with recurrent pterygium and a 46-year-old woman with primary pterygium underwent surgery using a novel autograft transfer technique that facilitates autograft suturing and ensures correct graft orientation. After removing the pterygium, three edges of the autograft were cut. The autograft was flipped first over the uncut edge and secured to the superior margin of the recipient bed with two sutures. Afterward, the fourth side of the graft was cut and the second flip was done over the sutured edge. Thus, the autograft was in correct surface and side orientation and was sutured to the recipient bed. This simple technique provides both easy transfer and correct orientation of the graft in autograft pterygium surgery.